Risk Factors for the Swiss Stock Market - Manuel Ammann; Michael Steiner (Swiss Journal of Economics and Statistics, 2008)
The four risk factors controlling for the market, size, value and momentum effect have become a state-of-the-art framework for various applications in financial markets research. However, previous work shows that these broadly recognized factors are country-specific. This paper develops and analyses the factors for the Swiss stock market from January 1990 to December 2005, building on a high quality dataset and taking into account specific characteristics of the Swiss stock market. We find robust premiums that are validated by comparisons to literature and US-data. The explanatory power of the factors is high, confirming their relevance to the Swiss stock market.
Keywords: G11; G12; G15; 330; Fama French; Carhart; Value; Momentum; Switzerland